The Exposure Rate Of Existing Shareholders, Underpricing And IPO Withdrawals At Borsa Istanbul: A Special Look At Opportunity Cost Of Issuance - Elma, Orhan Emre (Advances in Social Sciences Research Journal, 2020)
Capital markets play a key role in achieving the medium and long-term goals of companies to reach the point of comparison with their competitors in the world. Capital markets journey, which is so important for companies, can also be called a life and death war. Not every issuance application to regulators results in a positive outcome. Turkey is the third country that is experiencing the most IPO withdrawal, according to Bennouna's (2015) study. Reasons such as wrong timing of the issuance or not being able to create positive sentiment among stakeholders cause issuance withdrawals. Companies aim to guarantee the earnings of their first partners in the long term rather than bringing immediate positive returns for their new investors. For this reason, the damage suffered by the first partners in IPO is an important parameter in understanding capital markets, along with underpricing. In this study, 76 public offerings in Borsa Istanbul between 2005 and 2015 were examined according to Dolbin's (2013) methodology. The discount rate applied by the companies during this period is 22.86%, while the underpricing rate applied is around 4.3%. Results show that, opportunity cost of issuance, which is the loss suffered by the first partners is found to be only 1.3% at Borsa Istanbul. Also, the relationship between underpricing and opportunity cost of issuance is found to be 74.7%. The withdrawal rate have positive correlations of 36.6% and 40.4% with firm age and cost per share, respectively. Results also indicates that, withdrawal rates starts to diminish at hot markets when average market volatility rises.